TV 뉴스 브랜드 이미지가 시청의도에 미치는 영향 :상징적 속성과 기능적 속성을 중심으로 - 김정; 오세성; 진창현; Kim, Jeong; Oh, Sesung; Jin, Chang-Hyun (한국콘텐츠학회 논문지, 17(9), 2017)
This study aims to investigate the brand image of Korean TV news in terms of functional and symbolic attributes, to examine their interrelationships and their effect on audience' viewing intentions. A survey was conducted on 412 evening main news viewers of KBS1, SBS, and JTBC, and factor analysis and regression analysis were used. The results show that TV news brand personality was composed of three dimensions including enterprising, sincerity, and tradition. JTBC showed the highest mean value in terms of enterprising and sincerity over SBS and KBS1, and the lowest in tradition. The symbolic and functional attributes of the TV news brand image are highly correlated. Finally, the viewing intentions were determined in the order of news brand functional benefit, sincerity and enterprising personality factor. 본 연구는 한국 TV 뉴스 브랜드 이미지를 기능적, 상징적 속성의 측면에서 알아보고 이들의 상호 관계, 그리고 이들이 시청의도에 미치는 영향을 조사하는 것을 목적으로 하였다. KBS1, SBS, JTBC의 저녁 메인 뉴스 시청자 412명을 대상으로 서베이를 실시하였으며, 요인분석과 회귀분석을 사용하였다. 연구 결과에 따르면, TV 뉴스 브랜드 개성은 진취성, 정직성, 전통성 등 3개의 차원으로 구성되어 있었다. JTBC가 진취성, 정직성 면에서 SBS와 KBS1을 제치고 가장 높은 평균값을 보였고, 전통성 면에서는 가장 낮은 평균값을 나타냈다. 또한 TV 뉴스 브랜드 이미지의 기능적, 상징적 속성은 높은 상관관계를 보이며, 상호 동일한정도의 영향력을 미치고 있었다. 끝으로 시청 의도는 뉴스 브랜드 기능적 편익, 정직성, 그리고 진취성 개성 요인의 순으로 결정되었다.